Sulphate Resistance of Aerated Concrete Containing Palm Oil Fuel Ash as Partial Sand Replacement - Fadzil, Mat Yahaya; Khairunisa, Muthusamy; Saffuan, Wan Ahmad; Mohd Warid, Hussin (2015)
This research investigated sulphate resistance of aerated concrete containing palm oil fuel ash as partial sand replacement. Plain aerated concrete with 100% river sand was used as control specimen. Aerated concrete containing palm oil fuel ash was prepared by integrating 30% of the ground palm oil fuel ash as partial sand replacement. For strength determination, both mixes which cast in form of cubes were subjected to water curing up to 90 days. The compressive strength test was carried out in accordance to BS EN 12390-3 at 7, 28 and 90 days. The sulphate resistance of concretes was investigated by measuring the length change of mortar bars which immersed in 10% Sodium sulphate solution after water cured for 28 days. The measurement of length change was taken on weekly basis following the procedure outlined in ASTM C1012-13. Aerated concrete containing palm oil fuel ash exhibits continuous strength development as curing age become longer. Integration of palm oil fuel ash makes the concrete microstructure to be denser through formation of secondary C-S-H gel. The pozzolanic reaction also reduces amount of calcium hydroxide that can react with sulphate ion to form gypsum and ettringite which cause concrete deterioration. It is concluded that using ground palm oil fuel ash as partial sand replacement assist aerated concrete to exhibit higher compressive strength and better durability to sulphate attack.